Analisis Faktor-Faktor Yang Mempengaruhi Keberlangsungan Usaha UMKM di Kabupaten Sukoharjo - Putri, Tiara Salsabila Febriani Dika; Pamikatsih, Tri Ratna (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
This research aims to determine the influence of financial literacy, business capital and technology on the sustainability of MSME businesses in Sukoharjo Regency. This type of research method uses quantitative. The population of this research is the infinite population of all MSME business actors in Sukoharjo Regency. The sampling technique used the Rosceo formula to obtain a sample of 100 respondents. The analysis method uses quality test analysis methods (validity test, reliability test), classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), multiple regression analysis and hypothesis testing (t test and determinant coefficient test). The results of this research show that financial literacy, business capital and technology have a significant positive effect on business sustainability. Keyword : Financial Literacy, Business Capital and Technology